Analytical and Numerical Investigation of Embedded Through-section GFRP-Strengthened RC Beams with a Developed Bonding-based Model. (August 2022) - Van Hong Bui, Linh; Klippathum, Chanakan; Kongmalai, Nakares; Jongvivatsakul, Pitcha; Duc Ngo, Tuan; Stitmannaithum, Boonchai
Highlights: Bond model including general concepts for ETS bar–concrete interfaces is developed. Bonding-based behavior of ETS bars in strengthened beams is analytically studied. FEM coupled with bonding-based model for ETS-strengthened beams is proposed. Proposed FEM and shear strength model for ETS-strengthened beam are highly accurate. Abstract: This study analytically and numerically investigated the shear performance of rectangular concrete beams strengthened with embedded through-section (ETS) glass fiber-reinforced polymer (GFRP) bars. The key features of the bonding-based approach were first formulated and then validated by comparing their mechanism with the actual shear resistance mechanism of a strengthening system. Thereafter, a finite element method (FEM) incorporating the bonding-based approach was used to simulate the shear behaviors of ETS-GFRP-strengthened beams. Conversely, the shear crack angle model for ETS-GFRP-strengthened beams was empirically developed to enhance the accuracy of the prediction. The experimental data recently investigated by the authors regarding pullout tests and beam tests were utilized to verify the numerical and analytical results. The analyses indicate that the FE model coupled with the bonding-based approach is a universal and powerful method for simulating the behavior of ETS-GFRP-strengthened beams with and without anchorage. The results demonstrate the great potential of the analytical model, established on the basis of the bond mechanism, for assessment of the shear resistance of ETS-GFRP-strengthened beams.